Pengaruh Corporate Social Responsibility, Kepemilikan Institusional Dan Kepemilikan Manajerial Terhadap Harga Saham Dengan Profitabilitas Sebagai Variabel Moderasi - Pramana, Noval; Dahlan, Dede; Hikmah, Ma’rifatul (Politeknik Negeri Ambon, 2024)
In reality, not all companies especially the manufacturing sector, experience an increase in share prices on the market. Therefore, the aim of increasing share prices is the direction and target of the long term of a company which can be seen from the market value of its shares because investors measurements of companies can be seen from shifts in the share price of a company documented on the stock exchange which has had an IPO. So this has become a concentration tested by researchers to prove that the current year 2024 and the upcoming 2025 can be used as a reference and strategy in making investment decisions. The data created were annual reports and termination reports for manufacturing companies for the period 2018 – 2022 which were listed on the Indonesian Stock Exchange and company websites with the help of Microsoft Excel 2021 software and the Stata Program version 17. The sample collection technique applied purposive sampling technique with a total of 10 companies. The research results show that partially there is no significant influence between Corporate Social Responsibility (CSR) and Institutional Ownership on share prices, while there is a significant influence between Managerial Ownership on share prices. Furthermore, the Profitability Moderating Variable is able to strengthen Corporate Social Responsibility (CSR), Institutional Ownership and Managerial Ownership even though it does not have a significant influence on share prices.